(untitled) (Global Journal of Human-Social Science, 2026)
We propose an investigation of celebrated filmmaker Martin Scorsese’s oeuvre through the lens of painting and avant-garde. More specifically, we are interested in tracing connections between his work in the sixties and the Pop Art and Hyperrealism (or Nouveau Realism) movements from the period. We intend to demonstrate how many of the criticisms directed towards the director have also been pointed at these artistic movements. Therefore, we aim to understand the reasons for such by summarizing a brief history of the closeup — or more precisely, a few of the theorizations written about the technique. Lastly, we try to clarify some confusion that erupts from the use of “hyperrealism” as a category from contemporary scholars.We propose an investigation of celebrated filmmaker Martin Scorsese’s oeuvre through the lens of painting and avant-garde. More specifically, we are interested in tracing connections between his work in the sixties and the Pop Art and Hyperrealism (or Nouveau Realism) movements from the period. We intend to demonstrate how many of the criticisms directed towards the director have also been pointed at these artistic movements. Therefore, we aim to understand the reasons for such by summarizing a brief history of the closeup — or more precisely, a few of the theorizations written about the technique. Lastly, we try to clarify some confusion that erupts from the use of “hyperrealism” as a category from contemporary scholars.